Enamel Remineralization and Crystallization after Fluoride Iontophoresis. (April 2023) - Chaiwat, A.; Chunhacheevachaloke, E.; Kidkhunthod, P.; Pakawanit, P.; Ajcharanukul, O.
Early caries lesions consist of noncavitated subsurface demineralization caused by the dissolution of hydroxyapatite from the surface to the subsurface area of the enamel. Such lesions cannot be remineralized effectively by the conventional treatment. Thus, there is a need for a noninvasive technique capable of delivering the remineralizing agent to subsurface sites. For this purpose, fluoride iontophoresis (IP) using weak currents has been investigated with some conflicting results and no information on the crystal structure and composition. Because enamel remineralization involves the role of fluid from dentin, the presence of enamel fluid is necessary to determine the repair associated with the physiological condition. This study aimed to investigate structural and compositional characteristics, including the remineralizing effect of 5% sodium fluoride (NaF) IP with different polarities, cathodal iontophoresis (CIP), and anodal iontophoresis (AIP) for the treatment of natural enamel caries under simulated pulpal pressure. A bulk measurement of the crystal structure inside the lesion was first determined using calcium (Ca) K-edge X-ray absorption spectroscopy. IP with both polarities significantly promoted subsurface remineralization. The CIP generated a significant increase in the Ca/phosphorus ratio, and fluoride at the surface lesion significantly correlated with higher mineral density (MD) and more strengthening crystal structure of the lesion volume, while the lesion's MD and other impurities at the lesion surface, mostly the carbonate ions, affected the significant increase in MD with the unchanged structure of the lesion volume after AIP. The CIP of NaF is an ideal method for rapid enamel remineralization and recrystallization of fluoroapatite/fluorohydroxyapatite.